2021
DOI: 10.1186/s12887-021-02968-7
|View full text |Cite
|
Sign up to set email alerts
|

The association between low birth weight and dental caries among 11-to-13-year-old school age children in Ningbo, China

Abstract: Background The association between low birth weight (LBW) and dental caries is currently unclear. The aim of this study was to investigate the association of LBW with dental caries in permanent teeth in children of Ningbo city. Methods A total of 1975 children aged 11-to-13 years in Ningbo, China were enrolled in this cross-sectional study. LBW was defined as a birthweight< 2500 g. Ten dentists assessed the status of dental caries in permanent t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
1
1
1
Order By: Relevance
“…The Demirjian method shows a trend of overestimating chronological age in both the male and female groups of the southern China population, and the error was large, so it is considered unsuitable for the age estimation of the southern China population. This result is consistent with many studies in China 6 , 15 , 16 or Asian regions 17 . The Demirjian method was developed for age estimation of French-Canadians children, and the overestimation of the results in and around China suggests that the results of the age estimation are probably matched by the geographical proximity of the population.…”
Section: Discussionsupporting
confidence: 93%
“…The Demirjian method shows a trend of overestimating chronological age in both the male and female groups of the southern China population, and the error was large, so it is considered unsuitable for the age estimation of the southern China population. This result is consistent with many studies in China 6 , 15 , 16 or Asian regions 17 . The Demirjian method was developed for age estimation of French-Canadians children, and the overestimation of the results in and around China suggests that the results of the age estimation are probably matched by the geographical proximity of the population.…”
Section: Discussionsupporting
confidence: 93%
“…LBW refers to a newborn weighing ≤ 2.5 kg [ 28 ]. While previous studies on the association between LBW and dental caries in children have yielded inconsistent findings [ 28 30 ], our study demonstrated a positive association between LBW and caries. This relationship might be attributed to the higher prevalence of developmental defects observed in children with an LBW, as reported in previous studies [ 28 ].…”
Section: Discussioncontrasting
confidence: 62%
“…Dental caries are one of the most prevalent and dangerous oral diseases worldwide (GBD 2016 Disease and Injury Incidence and Prevalence Collaborators, 2017), particularly prevalence among adolescents (Kazeminia et al, 2020). Recent research has shown that the frequency of dental caries among Chinese teenagers ranges from 30.9% to 58.1% (He et al, 2022; Shi et al, 2022; Weng et al, 2021). Due to the irreversible nature of dental caries, preventing it during adolescence is essential, as it affects the quality of life and indirectly contributes to a decrease in the nation's productivity (Meier et al, 2017).…”
Section: Introductionmentioning
confidence: 99%